2021
DOI: 10.3389/fpsyg.2021.746324
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Digital Mental Health Interventions: Can Monetary Incentives Help?

Abstract: Digital mental health interventions (DMHI) are scalable and cost-effective strategies for increasing access to mental health care; however, dropout rates associated with digital interventions are high, particularly for open-access digital interventions. While some studies have focused on predictors of dropout from digital mental health programs, few studies have focused on engagement features that might improve engagement. In this perspective article, we discuss whether monetary incentives (MI) are one avenue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Online mental health interventions for PSP also have low participant adherence and completion, despite significantly reducing post-traumatic stress injuries and improving wellbeing, coping, and resilience (102). Although there are different facilitators of user engagement (118,119), the two most relevant to CWs are (1) the importance of developing programs that acknowledge their unique experiences and (2) consideration of interpersonal relationships.…”
Section: Enhancing Engagement By Acknowledging Unique Experiences And...mentioning
confidence: 99%
“…Online mental health interventions for PSP also have low participant adherence and completion, despite significantly reducing post-traumatic stress injuries and improving wellbeing, coping, and resilience (102). Although there are different facilitators of user engagement (118,119), the two most relevant to CWs are (1) the importance of developing programs that acknowledge their unique experiences and (2) consideration of interpersonal relationships.…”
Section: Enhancing Engagement By Acknowledging Unique Experiences And...mentioning
confidence: 99%
“…Time spent within the study may be a greater driver for attrition, as can be seen in the higher attrition rates for longer-term studies found in our results. However, research on the impact of monetary incentives on participants’ retention in digital health interventions is still in its infancy [ 96 ]. More needs to be done to understand how monetary incentives affect participants’ retention as well as effective engagement in the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…16 Low engagement, including accrual rates, uptake, and adherence, is an identified barrier to success, as it does not allow the expected benefits to be realised. 17,18 Guided delivery from health professionals can potentially increase engagement by enhancing patient motivation and accountability to adhere. 19 Guided interventions involve realtime (synchronous) or delayed (asynchronous) communication with health or research professionals, 20 often weekly or ad hoc, [20][21][22] potentially limiting scalability and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement can be characterised as the subjective experience of interest and attention, and extent of intervention usage 16 . Low engagement, including accrual rates, uptake, and adherence, is an identified barrier to success, as it does not allow the expected benefits to be realised 17,18 . Guided delivery from health professionals can potentially increase engagement by enhancing patient motivation and accountability to adhere 19 .…”
Section: Introductionmentioning
confidence: 99%